2022
DOI: 10.1080/10426507.2022.2085274
|View full text |Cite
|
Sign up to set email alerts
|

A green and novel method for the preparation of α-aminophosphonates using eggshell as catalyst. X-ray study

Abstract: An efficient and eco-friendly green methodology is developed for the synthesis of series of a-aminophosphonate derivatives from diverse aldehydes, anilines and triethyl phosphite by using environmentally benign and cost-effective Eggshells as solid heterogeneous base catalyst. The reaction is conducted by the stepwise one pot condensation through Kabachnick-Fields addition reaction in ethanol at room temperature during 25-30 min. High yield, short reaction time, solvent-free condition, waste to wealth, and opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…A wide range of catalysts has been employed for this reaction, from simple catalysts to structurally complex ones, some of which are not only expensive but also not environmentally friendly, such as scandium tris(dodecyl sulfate) [ 13 ], metal triflates [ 14 , 15 ], InCl 3 [ 16 ], Ln(OTf) 3 [ 17 ], SmI 2 [ 18 ] and AlCl 3 [ 19 ], among others [ 20 , 21 , 22 , 23 , 24 ]. However, over the years, several authors have reported that the KF reaction proceeds with good yields using biodegradable catalysts [ 25 , 26 ] or even catalyst-free and solvent-free conditions, offering an environmentally friendly reaction. In fact, the microwave (MW) promoted reaction catalyst-free and solvent-free has proven to be a remarkable alternative, given that, compared to conventional heating, it has multiple advantages such as shorter reaction times, high efficiency, cost-effectiveness and environmental friendliness [ 24 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of catalysts has been employed for this reaction, from simple catalysts to structurally complex ones, some of which are not only expensive but also not environmentally friendly, such as scandium tris(dodecyl sulfate) [ 13 ], metal triflates [ 14 , 15 ], InCl 3 [ 16 ], Ln(OTf) 3 [ 17 ], SmI 2 [ 18 ] and AlCl 3 [ 19 ], among others [ 20 , 21 , 22 , 23 , 24 ]. However, over the years, several authors have reported that the KF reaction proceeds with good yields using biodegradable catalysts [ 25 , 26 ] or even catalyst-free and solvent-free conditions, offering an environmentally friendly reaction. In fact, the microwave (MW) promoted reaction catalyst-free and solvent-free has proven to be a remarkable alternative, given that, compared to conventional heating, it has multiple advantages such as shorter reaction times, high efficiency, cost-effectiveness and environmental friendliness [ 24 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among numerous organophosphorus compounds, the phosphorus-containing derivatives of the alicyclic series are of particular interest, among which many valuable substances with practically useful properties have been synthesized. They can be used in various chemical transformations, and are also useful objects for studying some theoretical issues in organic chemistry [1][2][3][4][5]. Although the number of studies in the field of organophosphorus compounds is ever increasing, some interesting classes of organophosphorus derivatives of alicyclic acetylene-containing amines with various substituents both in the cycle and at the phosphorus atom, remain understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Although the number of studies in the field of organophosphorus compounds is ever increasing, some interesting classes of organophosphorus derivatives of alicyclic acetylene-containing amines with various substituents both in the cycle and at the phosphorus atom, remain understudied. The compounds of this class are always of interest to researchers due to the variety of chemical transformations and the prospect of their use in various fields of science and technology, which stimulates the development of new methods for the synthesis of their polyfunctional derivatives [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%